An Error Analysis of Students’ Writing in Narrative Text - Helmiyadi Helmiyadi; Nurul Kamaliah (Faculty of Social Science, Universitas Negeri Padang, 2021)
The aimed of the research was to find out the errors which were commonly made by the students of Sekolah Menengah Kejuruan Swasta Bustanul Yatama Syamtalira Bayu in their writing narrative text and to find out the causes of errors in their writing narrative text. This research useds a qualitative and quantitative approach. The population of this research was all the students of the Second year students of Sekolah Menengah Kejuruan Swasta Bustanul Yatama Syamtalira Bayu in academic year 2020/2021 consisted of 120 students and divided into 56 male students and 64 female students. The sample of this research selected by using random sampling technique by using lottery. In this study, only 20 students and one English teacher involved as the sample. The researcher use two kinds of instruments, they are test and interview. In analyzing the data, the writer used a percentage formula from Sudjana. Result of the research from test most of the first year students of Sekolah Menengah Kejuruan Swasta Bustanul Yatama Syamtalira Bayu made many errors in grammatical aspects in writing, a high percentage of errors was found in one out of three categories. The highest error category was tense errors. Moreover, the students felt difficult in getting ideas to begin free writing. The causes of errors were made by the students because of lack of interactive facilities is one of the problems to develop interactive classroom activities. Based on this reasoning, it can be concluded that many of the students made errors because of interlingual and intralingual transfer.